Word-Order and Features Inheritance: A Case Study of Standard Arabic - Alrashdan, Imran (DIRASAT: EDUCATIONAL SCIENCES, 2016)
This paper is an attempt to systemize Chomsky’s proposal of Features Inheritance (2005). It takes Standard Arabic as a Case Study. Accordingly, analysis is provided for Arabic SVO and VSO Clause Structure. Moreover, this study sheds light on Phasal Heads and Agreement. A question arises during the course of the study: “What defines a Phasal Head (at least with respect to Standard Arabic)?”. The analysis utilizes the Probe-Goal Analysis. The feature of Case plays a very significant role in the analysis presented here.